2013
DOI: 10.4338/aci-2012-09-ra-0037
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Manual versus Automated Data Collection Method for an Evidence-Based Nursing Practice Study

Abstract: SummaryObjective: The objective of this study was to investigate and improve the use of automated data collection procedures for nursing research and quality assurance. Methods: A descriptive, correlational study analyzed 44 orthopedic surgical patients who were part of an evidence-based practice (EBP) project examining post-operative oxygen therapy at a Midwestern hospital. The automation work attempted to replicate a manually-collected data set from the EBP project. Results: Automation was successful in repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This kind of analysis is suitable for qualitative studies where the researcher is interested in informants who have the best knowledge concerning the research topic, in this case, the users of Kindle product from Amazon. The methodology used in the comparison between manual and content analysis, from the end of the analysis, was also conducted in another study that identified same falsenegative and true negative results and it also concluded that automatic content analysis is far more useful, even if the accuracy is 100% accurate (Byrne et al, 2013). When using purposeful sampling, decisions need to be made about who or what is sampled, what form the sampling should take, and how many people or sites need to be sampled (Creswell, 2013).…”
Section: Methodsmentioning
confidence: 93%
“…This kind of analysis is suitable for qualitative studies where the researcher is interested in informants who have the best knowledge concerning the research topic, in this case, the users of Kindle product from Amazon. The methodology used in the comparison between manual and content analysis, from the end of the analysis, was also conducted in another study that identified same falsenegative and true negative results and it also concluded that automatic content analysis is far more useful, even if the accuracy is 100% accurate (Byrne et al, 2013). When using purposeful sampling, decisions need to be made about who or what is sampled, what form the sampling should take, and how many people or sites need to be sampled (Creswell, 2013).…”
Section: Methodsmentioning
confidence: 93%
“…To avoid the burden of false positive keywords, it is critical to detect negated clinical signs and family medical history. Both automatic and semi-automatic data extraction can lead to errors [7] but the semi-automated method reduces the eventuality that the researchers make two different interpretations of the exact same event, the final human check ensures that the algorithm is working properly and requires fewer human and computer resources to develop [8]. With the SDE the link between each extracted information and its document source and context is maintained, which ensures the possibility of data verification and traceability at any time.…”
Section: Discussionmentioning
confidence: 99%
“…Manual chart review is the gold standard method for gathering data for retrospective research studies ( 6 , 7 ). This process, however, is time consuming and necessitates personnel resources not widely available at all institutions ( 8 , 9 ). Prior to the pandemic, automated data extraction from the EHR utilizing direct database queries was shown to be faster and less error-pone than manual data extraction ( 8 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…This process, however, is time consuming and necessitates personnel resources not widely available at all institutions ( 8 , 9 ). Prior to the pandemic, automated data extraction from the EHR utilizing direct database queries was shown to be faster and less error-pone than manual data extraction ( 8 , 10 ). Nonetheless, data quality challenges related to high complexity or fragmentation of data across many EHR systems make automated extraction vulnerable ( 11–14 ).…”
Section: Introductionmentioning
confidence: 99%